Safe, at First: Acute Assessment and Management of Baseball-Related Head Injury by Field Personnel. (16th November 2020) - Sprau, Annelise; Slavin, Benjamin; Pierrot, Randall; Figueroa, Javier M; Komotar, Ricardo J; Jagid, Jonathan R; Thaller, Seth
Abstract: INTRODUCTION: Over 8.6 million children partake in organized and recreational baseball, well-regarded as "America's Past Time". Although improved equipment has reduced contemporary injury rates, nearly half of pediatric baseball injuries requiring hospitalization are due to head trauma. Sideline personnel at the youth and high school levels, often without advanced medical training, frequently act as first-responders in instances of acute craniofacial injury. Therefore, a rudimentary field management algorithm can serve to optimize acute patient care from sideline personnel. METHODS: An IRB-approved survey was distributed nationally to target field personnel working at youth, high school, collegiate, and professional baseball levels. Survey items included: comfort in assessing subtypes of acute craniofacial trauma (loss of consciousness [LOC], skull injury, orbital injury, nasal injury, and dental injury) via Likert scale, years of medical training, presence of an emergency action plan, and access to higher level care from emergency medical services (EMS) and/or a nearby hospital. RESULTS: Comfort with management of acute craniofacial injury differed significantly between on-field personnel at the amateur and professional levels, regardless of subtype of craniofacial trauma, P = .001. Experience with prior traumatic incidents also increased comfort levels with assessing and managing injuries, P = .026. The greatest difference in the ability to recognize skull injuries, was between amateurs and professionals, P = .0001. However, there was no significant difference in assessing LOC between amateurs and professionals, P = .33. Additionally, comfort with management of acute craniofacial injury significantly increased with years of medical training post-high school, and decreased time to EMS arrival across all playing levels, P = .033 and P = .017 respectively. Based on these findings, we were able to develop a rudimentary tool for on-field personnel to effectively assess and manage craniofacial injuries. CONCLUSION: We identified a significant disparity in comfort level between youth, amateur and professional baseball field personnel for identifying and managing acute craniofacial trauma. These personnel would benefit from on-field guidelines for real-time assessment.